2019
DOI: 10.5539/mas.v13n3p13
|View full text |Cite
|
Sign up to set email alerts
|

One Ultimate Journey? AKA the Huxley’s Method: Perspectives of (Ab)Users of Hallucinogens and Entheogens on Having Planned Pre-Mortem Psychedelic Trip

Abstract: Background: The surface web is a rich source of extensive data on populations of users and misusers of psychoactive substances including substances known as hallucinogens and entheogens. The internet and its social media websites can serve as a database upon which several hypotheses are applicable via thematic analytic and psychoanalytic studies. Materials and Methods: This study will deploy the use of an internet snapshot by inspecting, via thematic analysis, the comments of a population of psychedelic (ab)us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Further, the representation of psychoactive drugs—including psychedelics—in mass culture may influence the liberalization of interest or attitudes towards drugs and their use; mass culture relates to films, music, literature, everyday products, e.g., food, clothes, and cosmetics, in addition to role models, including actors, musicians, and celebrities [ 65 ]. However, psychedelics enthusiasts also declared a specific interest in those chemicals other than adolescents and young adults, for instance, using psychedelics for a planned pre-mortem psychedelic trip in the elderly and those with debilitating conditions, including malignant tumors; most psychedelic users recommended using DMT before death, while others suggested tripping on LSD, psilocybin and psilocybin mushrooms, and NBOMe compounds [ 69 ]. Researchers also confirmed that psychedelic users have tendencies to abuse high authority [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the representation of psychoactive drugs—including psychedelics—in mass culture may influence the liberalization of interest or attitudes towards drugs and their use; mass culture relates to films, music, literature, everyday products, e.g., food, clothes, and cosmetics, in addition to role models, including actors, musicians, and celebrities [ 65 ]. However, psychedelics enthusiasts also declared a specific interest in those chemicals other than adolescents and young adults, for instance, using psychedelics for a planned pre-mortem psychedelic trip in the elderly and those with debilitating conditions, including malignant tumors; most psychedelic users recommended using DMT before death, while others suggested tripping on LSD, psilocybin and psilocybin mushrooms, and NBOMe compounds [ 69 ]. Researchers also confirmed that psychedelic users have tendencies to abuse high authority [ 70 ].…”
Section: Discussionmentioning
confidence: 99%